2013
DOI: 10.1021/ac401786h
|View full text |Cite
|
Sign up to set email alerts
|

Hollow-Channel Paper Analytical Devices

Abstract: We present a microfluidic paper analytical device (μPAD) that relies on flow in hollow channels, rather than through a cellulose network, to transport fluids. The flow rate in hollow channels is 7 times higher than in regular paper channels and can be conveniently controlled from 0 to several mm/s by balancing capillary and pressure forces. More importantly, the pressure of a single drop of liquid (~0.2 mbar) is sufficient to induce fast pressure-driven flow, making hollow channels suitable for point of care d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 25 publications
1
143
0
5
Order By: Relevance
“…Equation 5 must then generally be solved numerically. However, in the absence of evaporation, it is simple to show 7 that this leads to a steady state capillary rise height H C = P C /ρg, allowing P C to be determined experimentally from a measurement of H C .…”
Section: Capillary Transport and Evaporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Equation 5 must then generally be solved numerically. However, in the absence of evaporation, it is simple to show 7 that this leads to a steady state capillary rise height H C = P C /ρg, allowing P C to be determined experimentally from a measurement of H C .…”
Section: Capillary Transport and Evaporationmentioning
confidence: 99%
“…Flow is driven by capillary action, channels have been defined using wax patterning, ink-jet printing, toner printing and boundary shaping [3][4][5][6], and devices have been fabricated with hollow and closed channels [7,8]. Detection has mainly been carried out using colorimetric assays for off-site analysis via the ubiquitous smartphone [9,10]; however, electrochemical detection has also been investigated [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Schilling et al [10] designed a fully enclosed paper-based devices and found that the amount of toner used to enclose channels could vary the liquid flow rate. Additionally, water solube pullulan films could serve as a controlled time shutoff system, through which a paper-based device with a time-dependent sequential release of reagents could be made [11] and a hollow channel applied in paper-based devices would enhance the flow rate of solution and reduce the analysis time [12]. However, the above researches just described the qualitative tendency of liquid flow in their devices, most of them might be affected by the evaporation in an open environment.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 gives an overview of various channel fabrication principles. In the simplest case, patterning can be achieved by cutting the paper [60][61][62] (Figure 6 a), which is not further discussed here. A more widely used approach is treatment with a hydrophobic material (Figure 6 b).…”
Section: Microfluidic Patterning Of Paper Substratesmentioning
confidence: 99%